A needs analysis of oral communicative skills in Mandarin by Malaysian hotel attendants / Wong Chih Khuan - Wong , Chih Khuan (2020)
Tourism is an important industry in Malaysia, contributing to one-sixth of the national gross domestic product for the past 10 years. Tourists from China made up the third largest group among the foreign visitors in Malaysia. Almost 25% of their expenditure is spent on accommodation, thus the management of many Malaysian hotels are promoting training on communicative Mandarin that focuses on hospitality language to their frontliners, i.e. the service attendants. Therefore, there is a need to identify the challenges faced by hotel service attendants when serving Chinese-speaking guests. The objectives of this research is (1) to identify the Mandarin communication skills needed by Malaysian hotel service attendants when interacting with Chinese-speaking tourists from China, (2) the Mandarin communication challenges in listening and speaking encountered by Malaysian hotel service attendants when interacting with Chinese-speaking tourists from China, and (3) Pinyin phoneme that they faced problem to differentiate or pronounce with. This study utilised the concurrent triangulation methodology to integrate both quantitative (questionnaire) and qualitative (interview) strategies to address the research questions. A total of 54 hotel service attendants from six hotels located in Klang Valley, Malaysia, were enrolled in the questionnaire survey, while 10 service attendants, training and human resource managers were engaged in the semi-structured interview. The results showed that there was a need for the hotel service attendants to learn communicative Mandarin that is specifically designed to serve the Chinese-speaking hotel guests. The service attendants had problems in listening to and speaking Mandarin when communicating with these guests, especially in differentiating and pronouncing difficult sounds like “Zi and Zhi”, “Ci and Chi”, “Si and Shi”. This research filled in a knowledge gap in Business Mandarin for the hospitality industry and served as a pioneering research for the field of Mandarin for Specific Purposes in Malaysia.